Deep Pelvic Endometriosis A Multidisciplinary Approach - De Nardi, Paola; Ferrrari, Stefano (Springer Milan : Imprint: Springer, 2011)
Deep pelvic endometriosis is one of the most severe expressions of a disease that may involve all the pelvic organs - bladder, ureters, rectosigmoid colon - causing debilitating symptoms and leading to impaired quality of life in young women. The chapters cover both diagnostic and therapeutic aspects of this disease. The central role of diagnostic imaging in surgical decision making is highlighted, as well as the difficulties involved in careful planning of surgical treatment, and special attention is paid to minimally invasive techniques. The paramount importance of a multidisciplinary team, involving the expertise of radiologists, gastroenterologists, and psychologists, as well as the skills of the gynecologist, urologist, and colorectal surgeon is underlined throughout the text.